Methylenedioxypyrovalerone (MDPV) impairs working memory and alters patterns of dopamine signaling in mesocorticolimbic substrates. (June 2020) - Bernstein, David L.; Nayak, Sunyl U.; Oliver, Chicora F.; Rawls, Scott M.; Rom, Slava
Highlights: MDPV increases dopamine- and glutamatergic- neurotransmission within VTA. MDPV promotes dopaminergic signaling within PFC; reduces such signaling within NAc. MDPV impairs novel object recognition. Abstract: Knowledge remains limited about how chronic cathinone exposure impacts dopamine systems in brain reward circuits. In the present study, a binge-like MDPV exposure that impaired novel object recognition (NOR) dysregulated dopamine markers in mesocorticolimbic substrates of rats, with especially profound effects on D1 and D2 receptor's and VMAT gene expression. Our data suggested that dopamine receptivity was reduced in the NAc but increased in the PFC and dopamine-producing VTA. The MDPV-induced impairment of NOR was prevented by a D1 receptor antagonist, suggesting that chronic MDPV exposure produces site-specific dysregulation of dopamine markers in the mesocorticolimbic circuit and memory deficits in the NOR test that are influenced by D1 receptors.